Case Report: Migralepsy: The Two-Faced Janus of Neurology - Sforza, Giorgia; Ruscitto, Claudia; Moavero, Romina; Ursitti, Fabiana; Ferilli, Michela Ada Noris; Tarantino, Samuela; Balestri, Martina; Vigevano, Federico; Valeriani, Massimiliano; Papetti, Laura (Frontiers in Neurology, 2021)
We report three cases of pediatric patients suffering from migraine aura triggered seizures. This entity, also called migralepsy, still does not have a unique definition today. Migraine and epilepsy are both episodic neurological disorders with periods of interictal well-being; this is indicative of similar pathophysiological mechanisms, such as increased neuronal excitation and ion channel dysfunction. The purpose of this paper is to discuss the clinical and instrumental features of migralepsy through the description of three clinical cases in which the symptoms of the usual migraine aura developed into a generalized tonic–clonic or focal seizure.